Development of professionalism vignettes for the continuum of learners within a medical and nursing community of practice - Penelope Smyth (Canadian Medical Education Journal, 2021)
Background: It is challenging to develop professionalism curricula for all members of a medical community of practice. We collected and developed professionalism vignettes for an interactive professionalism curriculum around our institutional professionalism norms following social constructivist learning theory principles.